Sphincterodiplostomum musculosum (Digenea, Diplostomidae) infectando Steindachnerina insculpta (Characiformes, Curimatidae) no reservatório de Chavantes, Sudeste do Brasil - Zago, Aline Cristina [UNESP] (2012)
This study aimed to report the infection by Sphincterodiplostomum musculosum metacercariae in Steindachnerina insculpta from the Chavantes Reservoir, medium Paranapanema River, municipality of Ipaussu, State of São Paulo, Brazil. Thirty specimens of S. insculpta were collected and 29 were infected with S. musculosum metacercariae (prevalence = 96.67%) in the eyes and visceral cavity. The mean intensity of infection and abundance were 96.6 ± 29.41 (7-846) and 93.3 ± 28.6 (0-846), respectively. Positive correlation was observed between parasite abundance in the eyes and standard length (rs = 0.5, p = 0.005), total weight (rs = 0.649, p = 0.0001), and condition factor (rs = 0.439, p = 0.0154). The high parasitism rates by S. musculosum metacercariae in S. insculpta can be an indicative that this fish species is highly susceptible to infection by this diplostomid, and even reflect the presence of a large abundance of the intermediate host. Moreover, S. musculosum metacercariae are reported for the first time in S. insculpta.